Kompetenselevering inom industrin medelst förstärkt verklighet - FELCZAK, DANIEL; LARSSON, MAGNUS (My University, 2018)
The education of a novice user in the usage of an industrial machine typically requires studies of information in written, or other non-interactive, form as well as the participation of a supervisor. This project has examined whether a tool based on augmented reality technology may constitute an alternative, that contributes with the necessary knowledge for the novice user while practical work is simultaneously carried out with the machine – that is to say achieves competence elevation. To investigate this question a tool was developed, Machine assistant, for the hardware platfrom HoloLens, which with the aid of augmented reality technology guides a user to the completion of machine related tasks. Furthermore the project has involved an exeperimet with the aim to evaluate whether the developed tool can be used for its intended purpose as well as prestudies of which potential drawbacks that are connected with this type of tool and of environmentally and ethically related aspects. The experiment with the developed tool affirmed that the tool type can be used for the intended purpose. The prestudy related to usability indicated that the tool is not competitive compared to for example movie instructions due to that the tool does not sufficiently improve knowledge procurement enough to motivate the extra user interaction the tool demands and because of the longer time it takes to reach the practical part of the knowledge procurement process. Further shortcomings that have been observed are connected to the hardware platform’s physical dimensions, battery time, comfortability and user-friendliness. The prestudy of environmental consequences shows that tools of this kind likely entail higher emissions of greenhouse gases compared to paper based alternatives. The prestudy pertaining ethical consequences indicated that the tool of the investigated kind contributes to the automation of society, which may entail reduction of opportunities for employment and the value of human competence. Other ethical consequences involve the risk of breachment of personal integrity as augmented reality technology continuously gathers data from its surroundings, data that may be sensitive. A conclusion of the project is that it has been confirmed that a tool of the investigated kind may be used for its intended purpose. However, a tool like Machine assistant, the technologies on which the tool type is reliant as well as hardware as the HoloLens likely require further development before tools like Machine assistant see broader use in industry.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science